Mass Spectrometric Studies of Fast Pyrolysis of Cellulose. Issue 3 (June 2015) - Degenstein, John C.; Hurt, Matt; Murria, Priya; Easton, McKay; Choudhari, Harshavardhan; Yang, Linan; Riedeman, James; Carlsen, Mark S.; Nash, John J.; Agrawal, Rakesh; Delgass, W. Nicholas; Ribeiro, Fabio H.; et al.
A fast pyrolysis probe/linear quadrupole ion trap mass spectrometer combination was used to study the primary fast pyrolysis products (those that first leave the hot pyrolysis surface) of cellulose, cellobiose, cellotriose, cellotetraose, cellopentaose, and cellohexaose, as well as of cellobiosan, cellotriosan, and cellopentosan, at 600°C. Similar products with different branching ratios were found for the oligosaccharides and cellulose, as reported previously. However, identical products (with the exception of two) with similar branching ratios were measured for cellotriosan (and cellopentosan) and cellulose. This result demonstrates that cellotriosan is an excellent small-molecule surrogate for studies of the fast pyrolysis of cellulose and also that most fast pyrolysis products of cellulose do not originate from the reducing end. Based on several observations, the fast pyrolysis of cellulose is suggested to initiate predominantly via two competing processes: the formation of anhydro-oligosaccharides, such as cellobiosan, cellotriosan, and cellopentosan (major route), and the elimination of glycolaldehyde (or isomeric) units from the reducing end of oligosaccharides formed from cellulose during fast pyrolysis.